Lithic industries of the first breeders’s establishment of Gobaad basin in the Rep. Of Djibouti : contribution of lithic technology in the characterization on the first Neolithic societies - (:unkn) unknown (My University, 2016)
This dissertation is focused of the technological analysis of several lithic assemblages from the Neolithic sites of the Gobaad basin, Republic of Djibouti. These ensembles were collected during recent surveys and excavations conducted within the framework of a French-Djiboutian project entitled “premières sociétés de production dans la Corne de l’Afrique” (first food-producing societies in the Horn of Africa). For many years, the late Prehistory of the Horn of Africa was only documented through surface collections and limited excavations that provided lithics and sometimes few hand-formed potsherds. In 1954, J.D. Clark grouped such materials from the former British Somaliland protectorate under the term Somaliland Wilton. No research has been conducted in Djibouti until 1984 and it is only since thirty years that emergence of food-producing societies can be addressed on the basis of material culture from dated contexts. In the Gobaad basin, Neolithic facies were identified based on important ceramic collections, the subsistence strategies of their makers were defined from two habitation sites, Asa Koma and Wakrita, which provided a wealth of data, including the earliest domestic animals bone remains known to this day in the Horn of Africa, dated to the middle of the 3rd millennium BCE. In this context, analysis of lithic collections from the Gobaad basin habitation sites is aimed to contribute to the characterization of the culture history of first food-producing societies but also to address the links between the technical behaviors of the knappers and the economic practices revealed by excavations.
Keywords: African Research